(untitled) (The Research of Medical Science Review, 2025)
Background and Objectives: Emotional disturbance is being increased in school children globally, which is alarming for all of us. Therefore, the current study investigates the relationship between intolerant behavior and sadness with the mediating role of anger and worry among children with minor emotional disturbances. Material and Methods: The current study was conducted from October 2019 to September 2020 among different schools of district Faisalabad, Pakistan. A total of 600 participants we targeted, 400 participants met the study inclusion and exclusion criteria. In the sample, boys were 200) and girls were 200. In our study, the participants' age range was 9 - 14 years. The Distress Tolerance Scale and Children Emotional Management Scale were administered. Data were analyzed using SPSS-V 26. Results: Results reveal that inhibition, dysregulation emotion, and coping subscales of anger, worry, and sadness significantly correlate with appraisal (p<.001), regulation (p<.001), tolerance (p<.001), and absorption (p<.001). Hierarchical regression analysis indicates subscales of distress tolerance, anger, and worry predicts sad emotions (R2= .51; F= 20.78; p<.001). Furthermore, the results indicate that anger and worry significantly mediate between intolerant behavior and sadness in emotionally disturbed school children (R2= .425; F (5,394) = 58.125, p< .001). Conclusion: It is concluded that low tolerance behavior increases the degree of anger and worry-related emotions high degree of anger and worry predicts the intensity of sadness in children.